Performance persistence and gamma convergence in absolute return funds in Poland over the period 2011-2018 - Machnik, Jadwiga (Utrzymywanie wyników inwestycyjnych oraz występowanie zjawiska gamma konwergencji na rynku funduszy absolutnej stopy zwrotu w Polsce w latach 2011-2018, 2020)
This article attempts to analyse the investment performance of absolute return funds in 2011-2018 in Poland from the point of view of their performance persistence and the occurrence of gamma convergence. Two research hypotheses were verified. The first one is that absolute return funds do not maintain their investment results, while the second deals with the occurrence of the gamma convergence phenomenon on the absolute return funds market. The research methods adopted, i.e. the contingency tables as a non-parametric method of measuring the maintenance of investment results, and gamma convergence as one of the convergence measures, allowed to reach appropriate conclusions. Performance persistence does not occur in most of the analysed cases. In the case of gamma convergence the obtained resultse indicated the occurrence of this phenomenon on the absolute return funds market
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 2-3, s. 41-54
Keywords: performance persistence; absolute return funds; gamma convergence; fundusze absolutnej stopy zwrotu; konwergencja gamma